2020
DOI: 10.1371/journal.pone.0237518
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of non-fistulous urinary incontinence among Ghanaian women seeking gynaecologic care at a teaching hospital

Abstract: The study assessed the prevalence and determinants of non-fistulous urinary incontinence among gynaecologic care seekers as well as its interference with everyday life activities of affected women. A cross-sectional study involving 400 women was conducted in a tertiary facility in Ghana. Urinary incontinence was assessed using the International Consultation on Incontinence Questionnaire-short form (ICIQ-SF) which has not been validated locally. The questionnaire was administered mostly in the Asante Twi langua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…One thousand two hundred and twenty-nine articles were screened, of which 1071 papers were excluded. A total of 148 publications were evaluated for eligibility, with 25 studies [14][15][16][17] being included in the current review [ Fig 1]. This study included a total of 17863 women from SSA.…”
Section: Study Selection Processmentioning
confidence: 99%
See 2 more Smart Citations
“…One thousand two hundred and twenty-nine articles were screened, of which 1071 papers were excluded. A total of 148 publications were evaluated for eligibility, with 25 studies [14][15][16][17] being included in the current review [ Fig 1]. This study included a total of 17863 women from SSA.…”
Section: Study Selection Processmentioning
confidence: 99%
“…As a results, in order to strengthen continence programs, health systems should be able to estimate the burden especially in a region with a frail health system, such as SSA. Hospital and community based-studies had been conducted for UI in SSA countries [14][15][16][17]. A significant limitation of these observational studies is likely under-estimation of the burden of UI in SSA [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing age has also been demonstrated as an independent risk factor for n-fUI in SSA [32,34]. Several changes occur in older women that contribute to the increased risk including hypoestrogenism, decreased urethral closure pressure, decreased bladder sensation, development of detrusor overactivity and increased nocturnal urine production, in addition to changes that occur with the patient's functional status such as impaired mobility [35].…”
Section: Non-fistulous Urinary Incontinencementioning
confidence: 99%
“…Non‐fistulous urinary incontinence was found to be more common in cross‐sectional studies from Nigeria, with adjusted odds ratios of 1.39 and 1.6 for overweight and obese women [29] and a twofold increased risk in patients who had a history of constipation [30]. Finally, studies in Ghana and Ethiopia have suggested up to four times increased risk of UI in women with a history of chronic cough [31,32]. Research has shown a growing burden of chronic respiratory disease in SSA [33] and this may become a more important factor for the development of female UI in the future.…”
Section: Aetiologymentioning
confidence: 99%